Improving growth and yield of Cucurbita argyrosperma with goat manure - Zondo, Nomfanelo; Ntuli, Nontuthuko R.; Mavengahama, Sydney; Van Jaarsveld, Corlina M. (Frontiers in Plant Science, 2025)
Cucurbita argyrosperma Huber is a traditional leafy vegetable crop where different plant parts are consumed by rural communities in South Africa especially in the northern KwaZulu-Natal, South Africa. Goat manure is a nutrient-rich organic fertilizer that is readily available in rural communities of KwaZulu-Natal. Little is known about the organic fertilizer requirements of C. argyrosperma. Therefore, this study aimed to determine the effect of goat manure application on the growth and yield of C. argyrosperma. A field experiment was conducted at the University of Zululand farm in northern KwaZulu-Natal in which C. argyrosperma was grown under six goat manure application rates (0, 5, 10, 15, 20 and 25 t ha–1) over two seasons in a randomized complete block design with four replications. Data were collected on vegetative growth traits (vine length, stem diameter, leaf area, number of branches and leaves, and leaf chlorophyll content), as well as marketable yield (shoot, fruit and seed fresh mass, shoot dry mass, and fruit and seed number). An analysis of variance test was performed on the pooled data to identify significant differences at p < 0.05 and the means were separated using Tukey’s test. Plants treated with 20 and 25 t ha–1 manure had significantly (p < 0.05) more branches and leaves, longer and heavier harvested shoots and a higher fruit number and mass and 100-seed mass than control. The remaining parameters increased with an increase in goat manure application, but not significantly. The yields obtained in this study were relatively low compared to typical yields for this crop and require further investigation. This study showed goat manure application could improve growth and yield of C. argyrosperma and ultimately contribute to food security in rural communities at affordable agronomic inputs.